Evaluating the quality of antenatal care and pregnancy outcomes using content and utilization assessment - Yeoh, Ping Ling; Hornetz, Klaus; Shauki, Nor Izzah Ahmad; Dahlui, Maznah (Oxford University Press, 2018)
Objective: To assess the adequacy of antenatal care (ANC) and its association with pregnancy outcomes using an approach that includes adequacy of both utilization and content. Design: Retrospective cohort study. Setting and Participants: Women attending ANC at public-funded primary health clinics where data were extracted from individual records. Methods: Adequacy of utilization assessment was based on the concept of Adequacy of Prenatal Care Utilization index; adequacy of content assessed the recommended routine care received by the women according to local guidelines. Association between adequacy and pregnancy outcomes was examined using binary logistic regression. Main Outcome Measures: Pregnancy outcomes included preterm birth and low birth weight. Results: Sixty-three percent of women showed higher than recommended ANC utilization; 52% had <80% of recommended routine care content. Although not statistically significant, the odds of preterm birth was lower among women with adequate level of utilization compared with inadequate (adjusted odds ratios (aOR) = 2.34, 95% confidence interval (CI) 0.45-12.16) and intensive levels (aOR = 3.27, 95% CI 0.73-14.60). Regarding adequacy of content, women who received inadequate level of care content were associated with higher prevalence of preterm birth (aOR = 3.69, 95% CI 1.60-8.55). Conclusion: The study shows inadequate content is associated with higher prevalence of preterm birth and suggests that inadequate utilization increases the risk of preterm birth. It demonstrates the relevance of using both utilization and content assessment in evaluating quality of ANC. Further studies are encouraged to review the methods used.